Knowledge and Preferences Regarding Antidepressant Medication Among Depressed Latino Patients in Primary Care. Issue 12 (December 2017) - Green, Bonnie L.; Watson, Maria Rosa; Kaltman, Stacey I.; Serrano, Adriana; Talisman, Nicholas; Kirkpatrick, Laura; Campoli, Marcela
Abstract : Abstract: US Latinos are less likely to utilize mental health services than non-Latino whites and to take antidepressant medications. This mixed-method study followed a subset ( N = 28) of a research sample of depressed Latino immigrant primary care patients, who took depression medication, with a telephone interview to study their knowledge about and experiences with antidepressant medications. Most (82%) reported taking medication for 2 months or more, and 75% reported feeling better, whereas more than half reported side effects. Most (61%) agreed that antidepressants are generally safe and helpful in treating depression (68%); however, many believed they could be addictive (39%). Fifty percent of patients who discontinued their medication did not inform their providers. Twelve of the 28 patients also participated in focus groups about interactions with providers and made suggestions for conveying information about antidepressants. Patients suggested videos as a format to disseminate medication information because they do not require written comprehension. Other patient recommendations are presented.